Transient dynamic analysis of cutter-head loads: effects of different cutter spacings during excavation - Kang, Minglei; Liu, Haining; Ma, Wenjia; Wang, Luqi; Zhou, Jianjun; Li, Miao (Frontiers in Earth Science, 2025)
As a critical component in achieving the rock-breaking function during the operation of Tunnel Boring Machines (TBM), the cutterhead inevitably generates significant vibrations during the rock-breaking process. These vibrations can lead to localized damage to the cutterhead and cause the abnormal failure of key components, which, in turn, may compromise the overall tunneling efficiency of the machine. This study investigates the load and vibration characteristics of the cutterhead during the rock-breaking process, employing large-scale physical model experiments conducted at varying cutter spacings. Real-time acceleration data from the cutterhead can be obtained through the monitoring system integrated into the TBM (Tunnel Boring Machine) experimental platform. The whole time-domain curves are stepped and periodic, as demonstrated by the test results. During excavation, the monitoring curves vibrate suddenly if the cutter-head becomes stuck or if rocks begin to fracture. The cutter-head primarily exhibits vibrations in the 0∼3 Hz range, characteristic of low-frequency oscillations. To obtain the real-time mechanical properties of the cutter-head, transient dynamic analysis was employed, utilizing the collected data as driving parameters. According to numerical simulation results, the vibration pattern during excavation is the superposition of random vibrations generated by rock breaking and the unloading of the tunnel face. Moreover, it is important to monitor the wear of the edge cutters throughout the boring operation in real-world construction scenarios. To prevent and control cutterhead vibration, it is recommended that the cutter spacing be as small as possible during the tunneling process. At a smaller tool spacing, the cutterhead will exhibit higher structural integrity, which may lead to a delay in the response of mechanical vibration. The conclusions presented offer valuable insights for the study of the mechanical properties and stability design of TBM cutterheads.